BUILDING UP STUDENTS’ SPEAKING SKILLS THROUGH BRAINSTORMING, EXPLORING, SHARING, TRANSFERRING KNOWLEDGE (BEST) STRATEGY - ida Ayu Made Sri Widiastuti; Ida Bagus Nyoman Mantra; Nengah Dwi Handayani (Lembaga Penelitian dan `Pengabdian Kepada Masyarakat (LPPM), 2022)
Speaking skills as a medium to develop and broaden horizons. Speaking skills, which are classified as productive language skills, are not only a medium for conveying various kinds of information and for expressing themselves. Speaking skills also apply media to broaden students' knowledge and insight into various fields of life. This study made use of a classroom action research design with two cycles of learning activities to improve students' speaking skills through BEST strategy. Data were collected through pre-test, post-test, and questionnaire. The results showed that the speaking skills of the students improved significantly from the first and second cycles when compared to the results of the pre-test. Therefore, the BEST strategy is considered effective for teaching speaking skills. This study implies that teachers should consider using BEST strategy in their classroom to build up students' speaking skills.